CALCULATION OF NITROGEN HEAT ADSORPTION ON VARIOUS CATALYSTS USING BET-CONSTANT (BET-C) DATA - Triyono Triyono; Wega Trisunaryanti; Oberlin Sidjabat (Testing Center for Oil and Gas LEMIGAS, 2008)
BET-C (Brunauer-Emmett-Teller-Constant) was used to calculate the heat of adsorption (ΔHads) of nitrogen gas on the various catalysts. The well-known Brunauer–Emmett– Teller (B.E.T.) equation is used primarily to determine the surface area from the physical adsorption of a gas on a solid surface. Surface area of catalysts was determined by using surface area analyzer (NOVA 1000). The BET-C included in the data is usually neglected or is not taken into account. However, by using the basic principles of the adsorption theory fitted with the functions based on the BET adsorption model, the important data of BET-C can be shown in this study. The value of the ΔHads (N2 ) for zeolite, H-zeolite, Pt/zeolite, Pt-Pd/zeolite, and Pt-Ce/zeolite calculated from the equation derived from BET-C are -6.43, -6.52, -8.78, -8.69, -9.71 and -9.52 kJ/mol, respectively.